2012
DOI: 10.1108/02635571211238482
|View full text |Cite
|
Sign up to set email alerts
|

The causal relationships between aspects of customer capital

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…The same was found in previous studies (e.g. Chan and Wang, 2012;Leal-Mill an et al, 2016). TMS, the moderating variable, strengthens the relationship between ITC and OP between SQ and OP.…”
Section: Hypotheses Testingsupporting
confidence: 89%
See 2 more Smart Citations
“…The same was found in previous studies (e.g. Chan and Wang, 2012;Leal-Mill an et al, 2016). TMS, the moderating variable, strengthens the relationship between ITC and OP between SQ and OP.…”
Section: Hypotheses Testingsupporting
confidence: 89%
“…Leal-Mill an et al (2016) found that ITC have an indirect effect on green innovation. Creating and analyzing innovative products and services using advanced information technology plays a dominant role in improving OP (Chan and Wang, 2012). Hence, there is a connection between the use of technology and SQ (i.e.…”
Section: Theoretical Background and Hypotheses Development 21 It Capa...mentioning
confidence: 99%
See 1 more Smart Citation
“…Service, both innovation and improvement, are essential in impressing and pleasing customers and neither should be disregarded (Tang, 2014). Although the prior studies address SQ (Chan and Wang, 2012;Tang, 2014Tang, , 2016, a lack of consensus exists on the SINO: SIMP-OP link, highlighting the necessity to study this area further. Therefore, the following hypotheses are formulated: H4a.…”
Section: Resourcebased View Theorymentioning
confidence: 99%
“…innovation and improvement). In prior studies, SQ impacts OP and is influenced by ITC (Chan and Wang, 2012) and SP (Albort-Morant et al, 2016). Companies are now being forced to embrace more environmentally friendly practices, regulations, consumers, staff and goods due to a growing focus on sustainability (Alkatheeri et al, 2021).…”
Section: Sequential Mediating Role Of Sp and Service Qualitymentioning
confidence: 99%